Minimizing Power Losses and Improving Voltage Profile Based on the Integration of Distributed Generation Units - Nguyễn Đình Phú; Nguyễn Anh Tuấn; Lê Chí Kiên; Phạm Đình Thái (Journal of Technical Education Science, 2025)
In this paper, an efficient optimization algorithm with the high stability and good convergence which was inspired by the intelligent movement of salp species in nature for finding food source, called salp swarm algorithm (SSA). This method is introduced for determining the optimal installation placement and capacity of grid-connected distributed generation units (DGs) to minimize power losses in the system, improve node voltage and reduce congestion on distribution lines. The obtained results from the simulation by SSA are shown to be superior to other compared algorithms such as particle swarm optimization (PSO) and artificial bee colony (ABC). In addition, this study also demonstrated the great benefits of integrating DGs in the distribution grid through cutting total power loss by up to 52.18%, enhancing node voltage from [0.8713, 1.00] (p.u) to [0.9627, 1.00] (p.u) and reducing the maximum branch current by up to 32.59% in the large-scale distribution system of the IEEE 85-node.